Measurements of top-quark pair differential cross-sections in the e[my] channel in pp collisions at √s = 13 TeV using the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2017)
This article presents measurements of tt¯ differential cross-sections in a fiducial phase-space region, using an integrated luminosity of 3.2 fb−1 of proton–proton data at a centre-of-mass energy of s√=13 TeV recorded by the ATLAS experiment at the LHC in 2015. Differential cross-sections are measured as a function of the transverse momentum and absolute rapidity of the top quark, and of the transverse momentum, absolute rapidity and invariant mass of the tt¯ system. The tt¯ events are selected by requiring one electron and one muon of opposite electric charge, and at least two jets, one of which must be tagged as containing a b-hadron. The measured differential cross-sections are compared to predictions of next-to-leading order generators matched to parton showers and the measurements are found to be consistent with all models within the experimental uncertainties with the exception of the Powheg-Box + Herwig predictions, which differ significantly from the data in both the transverse momentum of the top quark and the mass of the tt¯ system.